2007
DOI: 10.1074/jbc.m703742200
|View full text |Cite
|
Sign up to set email alerts
|

Live Cell Imaging of Outward and Inward Vesiculation Induced by the Complement C5b-9 Complex

Abstract: Cells resist death induced by the complement membrane attack complex (MAC, C5b-9) by removal of the MAC from their surface by an outward and/or inward vesiculation. To gain an insight into the route of MAC removal, human C9 was tagged with Alexa Fluor 488 and traced within live cells. Tagged C9-AF488 was active in lysis of erythrocytes and K562 cells. Upon treatment of K562 cells with antibody and human serum containing C9-AF488, C9-AF488 containing MAC bound to the cells. Within 5-10 min, the cells started sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 48 publications
(20 reference statements)
4
73
0
Order By: Relevance
“…Complement activation has previously been linked with the generation of microparticles, 8,9 but the results of the current studies also demonstrate that microparticles themselves can directly activate the complement system. Although immunoglobulin and complement proteins have been detected on the surface of microparticles from apoptotic cells 14 and microparticles isolated from patients with inflammatory diseases, [15][16][17] these previous studies did not Microparticles from the supernatant of unmanipulated or CsA-treated cells were exposed to serum, and C3 deposition on the microparticles was assessed by Western blot analysis using a polyclonal antibody to C3 and a monoclonal antibody to C3d.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Complement activation has previously been linked with the generation of microparticles, 8,9 but the results of the current studies also demonstrate that microparticles themselves can directly activate the complement system. Although immunoglobulin and complement proteins have been detected on the surface of microparticles from apoptotic cells 14 and microparticles isolated from patients with inflammatory diseases, [15][16][17] these previous studies did not Microparticles from the supernatant of unmanipulated or CsA-treated cells were exposed to serum, and C3 deposition on the microparticles was assessed by Western blot analysis using a polyclonal antibody to C3 and a monoclonal antibody to C3d.…”
Section: Discussionsupporting
confidence: 51%
“…6,7 Complement activation on the cell membrane can induce cells to release microparticles. 8,9 Although complement proteins can be detected on the surface of microparticles released from apoptotic and injured cells, 10 less is known regarding whether microparticles from specific cell types themselves can cause complement activation. We hypothesized that injury of endothelial cells induces the release of complement-activating microparticles into the circulation.…”
mentioning
confidence: 99%
“…They, most likely, encompass plasma membrane regions situated in the vicinity of SLO-induced pores. 14 The annexin A1-positive Ca 2 þ 'hot spots' were restricted to small regions within the plasma membrane, which suggested that the diffusion between these structures and the cytoplasm was effectively limited. Annexins are able to promote fusion of adjacent membranes in the presence of Ca 2 þ .…”
Section: Resultsmentioning
confidence: 99%
“…For example, a considerable body of evidence indicates that one of the ways that cancer cells inhibit C-mediated killing is by expressing increased levels of C control proteins (11, 49 -53). Moreover, when sublytic amounts of C are used to attack nucleated cells, the cells can respond by implementing strategies to enhance their resistance to subsequent assaults by C (46,48,53).…”
Section: Discussionmentioning
confidence: 99%
“…Reaction of nucleated cells with sublytic amounts of C can lead to the rapid release of vesicles that are enriched in the MAC, and this process appears to be mediated by the mitochondrial heatshock protein 70, also called mortalin (45)(46)(47)(48). It is important to determine whether the streamer production we have seen could be related to, or is simply another manifestation of, the vesicle release process described by Morgan, Fishelson, and their colleagues (45)(46)(47).…”
Section: Investigation Of Possible Mechanisms Of Streamer Formationmentioning
confidence: 99%